Implementation of an IoT-Based Drip Irrigation System for Cucumis melo Cultivation in Greenhouse Environments: Initial Evaluation - Syukur Toha Prasetyo; Syaiful Khoiri (CIB Nusantara, 2025)
The cultivation area for melon (Cucumis melo L.) in Indonesia has been declining despite increasing consumption, necessitating innovative production techniques. This study evaluates the application of the Internet of Things (IoT) in greenhouse-based melon cultivation using an automated drip irrigation system. The system integrates solar-powered sensors and microcontrollers to monitor temperature, humidity, pH, and Total Dissolved Solids (TDS), with real-time feedback via the Blynk application. Melon plants were grown hydroponically (cocopeat: sawdust 1:1) in a 6×12 m greenhouse at P4S Bumiaji Sejahtera, Batu, East Java. Results showed that measured temperature (21.9–30.3 °C) and humidity (57–99.9%) were generally within optimal ranges for melon growth. The TDS of the nutrient solution (≈1860–1894 ppm) was near the recommended 1600–1800 ppm for hydroponic melon. The humidifier operated as intended (ON at 50–70% RH, OFF at 80–90%). Blynk connectivity allowed real-time data display only when the internet was available. Water discharge from the drippers varied widely (10–60 mL/min) across seven points, attributed to emitter placement and backflow. Camera feeds from the greenhouse were viewable in the Blynk app when online, but not when offline. The IoT drip-irrigation system functioned and provided remote monitoring, but sensor issues and uneven flow limited optimal automation. Future work should improve sensor calibration, flow uniformity, and integrate fertigation.